2018
DOI: 10.1177/1363461518804094
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Comparison of Climacteric Symptoms, Health-Seeking Behavior, and Attitudes towards Menopause Among Mosuo Women and Han Chinese Women in Yunnan, China

Abstract: Cultural *YZ and XZ contributed equally. background has been shown to influence climacteric symptoms of women. This study compares various characteristics of climacteric symptoms, illness conception, health-seeking behavior, and attitude towards menopause of Mosuo women, a Chinese ethnic minority with a matriarchal structure, and Han Chinese women, the majority ethnic group of China with a patriarchal structure. Through convenience sampling, 51 Mosuo and 47 Han women ages 40 to 60 completed a sociodemographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…They reported a significant difference in attitudes toward menopause between the ethnicities, suggesting that women in the minority ethnicity group had more negative attitudes toward menopause compared with the women who belonged to the majority ethnicity group ( P < 0.001). The subscale analysis revealed that feminist views ( P < 0.05) and society's views ( P < 0.01) were the subscales of attitudes toward menopause that were significantly higher among the major ethnicity compared with the minority ethnicity 26 …”
Section: Resultsmentioning
confidence: 95%
“…They reported a significant difference in attitudes toward menopause between the ethnicities, suggesting that women in the minority ethnicity group had more negative attitudes toward menopause compared with the women who belonged to the majority ethnicity group ( P < 0.001). The subscale analysis revealed that feminist views ( P < 0.05) and society's views ( P < 0.01) were the subscales of attitudes toward menopause that were significantly higher among the major ethnicity compared with the minority ethnicity 26 …”
Section: Resultsmentioning
confidence: 95%
“…Studying the effect of the long-term absence of ovarian hormone produced by ovariectomy in mice and rats on anxiety-and depression-like behaviors and the underlying neurochemical and anatomical changes is necessary in understanding neuropsychiatric disorders among women undergoing oophorectomy. Considering that in experimental animals, it is possible to discard the socio-cultural influence that menopause could have on women and its contribution to their emotional and affective disorders (Afridi, 2017;Zhang et al, 2019), the surgical menopause model in mice and rats may provide new evidence for the neurobiological mechanism resulting from ovariectomy (oophorectomy in women) in the long-term. Therefore, this model can be used to explore potential therapeutic strategies to ameliorate emotional and affective symptoms, in addition to physiological, histological, structural, and neuropsychiatric disorders occurring in women subjected to surgical menopause.…”
Section: Discussionmentioning
confidence: 99%
“…The results are consistent with previous epidemiological studies that Mosuo women generally have better mental health than other ethnic groups (Xu et al, 2018;Yang et al, 2018). For instance, the incidence of depression during perimenopause in Mosuo women is lower than that in Han women (Zhang et al, 2013(Zhang et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%